A model for the enhancement of autonomy - SILVA, Walkyria Alydia Grahl Passos Magno e (2015)
This article presents an innovative model for the enhancement of learner autonomy and shows some of its results and challenges. The model entails investigation of problematic areas of individual students' foreign language learning processes, identification of their privileged learning styles, use of technological tools to improve learning autonomy, development of a wider range of language learning strategies, and implementation of self-monitoring and self-evaluation routines. This model has been applied for the last three years with undergraduate students, earning a B.A. in Modern Languages (English, French or German), who will become foreign language teachers in elementary and high schools in Brazil. Results are threefold: first, the model has proven its efficiency in providing scaffolding for students autonomous language learning; second, autonomy developing experiences lived by subjects who are studying to be teachers can be mirrowed in their future professional lives with their own students; and thirdly, data derived from the participants in the study can shed some light into the variety of ways people learn in the local context.